Influence of Soil Properties on Plant-Parasitic Nematode Abundance in the Rhizosphere of Pepper Plants in Niger State, Nigeria - A.S. Paiko; L.Y. Bello; A.C. Wada; M. S. Gwam (Current Research Progress in Agricultural Sciences Vol. 10, 2025)
Pepper is a member of the Solanaceae family and belongs to the genus Capsicum. The genus Capsicum is comprised of approximately thirty-one species of which five species have been domesticated and include C. annuum L., C. baccatum, C. chinense, C. frutescens L., and C. pubescen. It is a significant agricultural crop because of its economic importance, and nutritional and medicinal value of its fruits. It has a high content of natural colours and phenolic compounds. A survey was conducted to investigate the effect of physico-chemical properties of soil on the incidence and infestation of plant-parasitic nematodes on Pepper, Capsicum spp from two local government areas (LGAs) of Niger State, Nigeria. One hundred and twenty soil and plant root samples were randomly collected from pepper fields and examined using the Cobb sieving method. During the surveys, root and soil samples were carefully collected from 30 different localities having extensive pepper cultivation from randomly selected fields to assess the incidence, intensity and distribution pattern of plant parasitic nematodes. Results showed that six genera of plant-parasitic nematodes were recorded. The most frequently observed and widely distributed nematode species were Helicotylenchus multicinctus followed by Meloidogyne spp. and Scutellonema bradys with frequencies of occurrence of 48.2, 34.8 and 12.6 % respectively. The highest nematodes population density of 405 in 100 ml soil was recorded from Maje followed by Annaba with 205, both in Magama LGA, while the lowest nematodes of 20 in 100ml soil were recorded from Nagwamatse in Kontagora LGA. Correlation analysis revealed a weak relationship between soil physico-chemical properties and nematode population density with a maximum value of r = 0.38. Increased soil acidity of pH 4.5-5.4 led to faster reproduction of PPNs leading to huge crop loss The results also showed that apart from the direct influence of the host plant, soil properties play an important role in the distribution, abundance, and structure of plant parasitic nematode communities. This demonstrates the potential of nematodes as bio-indicator organisms of soil health. The present study has established the occurrence and prevalence of plant parasitic nematodes, which may consequently cause severe yield reduction in pepper. The study has also confirmed the importance of parasitic nematodes associated with pepper in the study areas as well as soil property influence On the PPNs.